The Influence Of Marketing Mix (7PS) To Customer Satisfaction Customer Loyalty And Customer Retention At Coffeshop - Tasya Rachmadhini Fajrin; Atik Aprianingsih (UNIVED Press, 2024)
This study delves into Indonesia's coffee shop industry, investigating the interplay between the 7P Marketing Mix elements and customer satisfaction, loyalty, and retention. Leveraging a quantitative methodology, data was gathered from Google form to construct a Structural Equation Modeling (SEM) analysis. The findings underscore the significant impact of price, people, process, and physical evidence on customer satisfaction, while revealing that product, place, and promotion exhibit nuanced effects within this context. Importantly, the research confirms the robust relationship between customer satisfaction and loyalty, elucidating the pivotal role of loyal customers in bolstering sustained retention. This comprehensive analysis sheds light on strategies imperative for businesses within the competitive Indonesian coffee market, emphasizing the need to prioritize customer satisfaction and loyalty to ensure enduring success.